Establishing phosphorus critical values for tomato (Solanum lycopersicum) fertilization with phosphate fertilizers on the Sudan savanna soils using three soil phosphorus extraction methods and field experimentation in Kano State, Nigeria - Yusuf, Yahaya Mohammad; Madukwe, Donald Kelechi; Kebede, Fassil (Frontiers in Agronomy, 2023)
Phosphorus (P) is an essential nutrient for tomato production, as it stimulates root growth by improving water use efficiency and nutrient uptake. Besides, it helps in controlling the metabolic processes of ATP (energy), sugars, and nucleic acids. As a result, it is imperative to effectively manage P requirement of tomatoes for bolstering its productivity. This study was conducted with the objectives of evaluating the effectiveness of three different soil P testing methods which are suitable for the soils of Kano State, Nigeria, and developing a critical P value for fertilizer recommendation for tomatoes. Accordingly, sixty topsoil samples were collected for soil available P testing according to Bray II, Mehlich 3, and Olsen methods. Moreover, in order to establish the P critical (Pc) value for tomatoes, a field experiment was conducted with seven different rates of P using triple super phosphate fertilizer (TSP), viz., 0, 15, 30, 45, 60, 75, and 90 kg P/ha, laid out in a randomized complete block design with three replications on fifteen experimental sites representing the various agroecological zones of the State. Phosphorus fertilizer was applied and incorporated into the soils one week before tomato transplanting. Then, soil samples from 0-20 cm depth were taken 3 weeks after transplanting from all the plots across the experimental sites for separate Mehlich 3, Bray II, and Olsen extractable P analysis to determine the critical soil P (Pc) test. The study revealed that available P was varied and increased in the order of Olsen (2.19 ppm) < Mehlich 3 (5.37 ppm) < Bray II (5.44 ppm). Furthermore, the study showed that Pc values were 17.00, 14.00, and 4 ppm for Mehlich 3, Bray II, and Olsen respectively. Finally, Bray II was a more reliable method for estimating the available P on moderately acid soils as it showed the highest correlation r = 0.83 with the relative yield of the tomatoes. The equation developed for the P fertilizer recommendation (Pr) for tomato for Kano State was found to be “Pr (kg P2O5 ha-1) = (14.0-Po) x 9.02” based on Bray II method